THE OBLIGATION TO LEGISLATE CRIMES AGAINST HUMANITY IN THE COLOMBIAN CRIMINAL CODE - Arango Haupt,Tribunal Penal Internacional, Haia, Holanda, Susana (2012)
The Republic of Colombia has suffered the struggles of an internal armed conflict for more than forty years. Through time, different Colombian governments have tried to negotiate peace and begin the process of demobilization with various illegal guerrilla and paramilitary groups. The most successful peace process with a guerilla group has been the reincorporation into civilian life of the rebel group M19 in 1990. However, since then little has been achieved in terms of peace. Since 1990, various governments have attempted to conduct peace negotiations with other illegal armed groups. The most relevant of such efforts were the peace negotiations of 1998 to 2002 between the administration of former Colombian president Andrés Pastrana and the Armed Rebel Forces of Colombia (FARC, the biggest guerrilla group). Unfortunately, these negotiations failed and in the meanwhile the FARC gained territorial power. In fact, since then both the FARC and paramilitary groups increased their numbers. In 2002, the government of former president Álvaro Uribe initiated a process of transitional justice. Its principal goal was the demobilization of the paramilitary group AUC (Colombian United Self-defense Group) and achieved justice. Little has been done in this regard. Poor results have been achieved throughout the prosecutions which have been done until now.